(3GdEaUGM aj TQM cJGH GdEjVGMs - (3CHh GdMSjf Hf CHi GdQHjYs; (3GHf GdHQPYjs
(3ChdgG (B:s
(3jHOC HHGH Yde MQha GdRjGOI s
(3BNQgG (B:s
(3ceG MPahG GddGe GdChdi ef XddJ abGdhG CXdJ hgh eY Pdc dG jcGO jYQa hdjS eSehYkG ef aUMGFge Je GdSaQ GdNGeS ef TQM GdEjVGM hHJeGeg Je LejY GdOjhGf s
(3GdfSNI HgG MhGTs
(3dgG fSNI eagQSI JMJ Qbe (B14 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs